The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/jocn.13606
|View full text |Cite
|
Sign up to set email alerts
|

Medication communication between nurses and doctors for paediatric acute care: An ethnographic study

Abstract: Understanding of the complexities affecting medication communication between nurses and doctors helps to ensure interprofessional respect for each other's roles and inherent demands. Interdisciplinary education delivered in healthcare organisations would facilitate greater clarity in communication related to medications. Encouraging the use of concise, clear words in communication would help to promote improved understanding between parties, and accuracy and efficacy of medication management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 42 publications
4
22
0
1
Order By: Relevance
“…However, in our study, the frequent reasons for communication delay were found more in the false assumption of colleagues` work processes (26%) and lack of task coordination than technical access barriers (5.2%). Similar to our findings, Borrott et al (2017) reported nurses’ frustration in the lack of verbal enforcement of changed digital prescriptions. To avoid delays in the implementation of prescriptions in the future, enforced verbal communication is needed, especially outside the ward round periods (Borrott et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, in our study, the frequent reasons for communication delay were found more in the false assumption of colleagues` work processes (26%) and lack of task coordination than technical access barriers (5.2%). Similar to our findings, Borrott et al (2017) reported nurses’ frustration in the lack of verbal enforcement of changed digital prescriptions. To avoid delays in the implementation of prescriptions in the future, enforced verbal communication is needed, especially outside the ward round periods (Borrott et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…In the PuBMed database, a search using the keywords medication incident OR medication error AND communication yielded 11 hits in the year 2000, 97 hits in 2010 and 127 hits in 2018. Errors in medication communication being linked with medication incidents have been studied from specific viewpoints, such as within diverse care‐provider settings or between them (Petersen, Foged, Madsen, Andersen, & Nørholm, 2018), in speciality practices (Keers et al, 2018;Liu, Manias, & Gerdtz, 2014;Manias, Cranswick, et al, 2019;Tobiano, Chaboyer, Teasdale, Raleigh, & Manias, 2019) or among specific patient age group settings (Borrott et al, 2017). Evidence of medication communication exists for a variety of care process situations (Braaf, Rixon, Williams, Liew, & Manias, 2015a;Liu, Manias, & Gerdtz, 2012;Manias, Braaf, et al, 2019;Yu, Li, Gao, Liu, & Lin, 2018), and concerning a diverse range of communication methods (Foged, Nørholm, Andersen, & Petersen, 2017;Redley & Botti, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the differences seen in the domains of meaning and preferences for partnership, the domains of biomedical cause, fault, control and effectiveness of natural treatments are areas where mothers' perception and the providers' understanding of this perception were the same. The years of experience in both physician and advanced practice providers groups (Table ) likely contributed to improved agreement, as is consistent with previous research in this field (Borrott et al, ). Additionally, agreement between providers and parents was likely impacted by the diversity of roles within the treatment team, as well as the consistency in the providers during hospitalisation.…”
Section: Discussionsupporting
confidence: 86%
“…It is evident in this study that advanced practice providers have an understanding of mothers' perception of illness. Nurses and doctors have different communication styles (Borrott et al, ) and have fundamental differences including status, gender, training and patient care responsibilities (Thomas et al, ). Many similarities were found between all healthcare providers and mothers, which may indicate that paediatric providers in general have a relationship with their patients and families that fosters understanding regarding perception of illness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation